In vitro antimicrobial activity of selected mouthwashes on Streptococcus species isolated from adult patients with dental caries - Francisca Nwaokorie; UO Edet; OM Odeniyi; UC Ndu; O Alabi; KA Umeizudike (Babcock University Medical Journal)
Objective: Dental caries is a preventable oral disease with economic burdens and effects on the quality of life. The study aimed to isolate Streptococcus species implicated in dental caries and also evaluate the antimicrobial potential of three brands of mouthwashes.